Survey on Spawning Characteristics of Rice Planthoppers in Different Rice Varieties - Liang, Lv; Peitao, Li; Ju, Luo; Shu, Zhang (Plant Diseases and Pests(植物病虫害研究：英文版), 2013)
The fecundity and spawning locations of rice planthoppers in several rice varieties were surveyed in the test. The results showed that spawning behavior of rice planthoppers obeyed obvious niche distribution; rice planthopper preferred to lay eggs in the leaf sheath with spawning mark distance more than 20 cm, while they liked to lay eggs in the leaves with spawning mark distance of 10 - 20 cm. The average fecundity in leaf sheaths was obviously higher than that in leaves, indicating that leaf sheaths were more suitable for spawning of rice planthoppers than leaves.